2020
DOI: 10.1016/j.isci.2020.101472
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS18 Deficiency Leads to Pulmonary Hypoplasia and Bronchial Microfibril Accumulation

Abstract: Summary ADAMTSs (a disintegrin and metalloproteinase with thrombospondin motifs) are secreted metalloproteinases that play a major role in the assembly and degradation of the extracellular matrix (ECM). In this study, we show that ADAMTS18, produced by the epithelial cells of distal airways and mesenchymal cells in lung apex at early embryonic stages, serves as a morphogen in lung development. ADAMTS18 deficiency leads to reduced number and length of bronchi, tipped lung apexes, and dilated alveoli.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Additionally, many of these genes are potential transcription factors and growth factors in lung development. For example, Scgb3a2 is a growth factor in lung promoting both early and late stages of fetal lung development (Kurotani et al, 2008), Adamts18 is pivotal in airway branching morphogenesis (Lu et al, 2020), and Hmga2 is required for WNT signaling during lung development (Singh et al, 2014). The data suggest that the lack of embigin causes delays rather than structural defects in lung development.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, many of these genes are potential transcription factors and growth factors in lung development. For example, Scgb3a2 is a growth factor in lung promoting both early and late stages of fetal lung development (Kurotani et al, 2008), Adamts18 is pivotal in airway branching morphogenesis (Lu et al, 2020), and Hmga2 is required for WNT signaling during lung development (Singh et al, 2014). The data suggest that the lack of embigin causes delays rather than structural defects in lung development.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that some ADAMTS (e.g., ADAMTS-6, ADAMTS-10, and ADAMTS-17) proteases can bind to fibrillin-1 or fibrillin-2 or both (Hubmacher et al, 2017;Cain et al, 2016;Hubmacher and Apte, 2011;Kutz et al, 2011). Recently, we found that Adamts18 modulates bronchial fibrillin microfibril formation by binding to fibrillin-1 (Lu et al, 2020a). In this study, the levels of fibrillin-1 were found to be iScience Article significantly increased in E14.5 CCAs of Adamts18 À/À mice, and Adamts18 À/À CCA was found to have disordered elastic fibers and reduced carotid blood pressure (Figure 5).…”
Section: Adamts18-mediated Ecm Homeostasis In the Differentiation Of Cnccs To Vsmcsmentioning
confidence: 90%
“…RNA in situ hybridization (ISH) was performed as described previously (Lu et al, 2020a;Zhu et al, 2019). Briefly, mouse embryos were fixed in 10% neutral buffered formalin for 24 h at room temperature (RT) and paraffin-embedded following standard methods.…”
Section: Rna In Situ Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations